A Memory B Cell Crossmatch Assay for Quantification of Donor‐Specific Memory B Cells in the Peripheral Blood of HLA‐Immunized Individuals. Issue 10 (3rd May 2017) - Karahan, G. E.; de Vaal, Y. J. H.; Krop, J.; Wehmeier, C.; Roelen, D. L.; Claas, F. H. J.; Heidt, S.
Abstract : Humoral responses against mismatched donor HLA are routinely measured as serum HLA antibodies, which are mainly produced by bone marrow–residing plasma cells. Individuals with a history of alloimmunization but lacking serum antibodies may harbor circulating dormant memory B cells, which may rapidly become plasma cells on antigen reencounter. Currently available methods to detect HLA‐specific memory B cells are scarce and insufficient in quantifying the complete donor‐specific memory B cell response due to their dependence on synthetic HLA molecules. We present a highly sensitive and specific tool for quantifying donor‐specific memory B cells in peripheral blood of individuals using cell lysates covering the complete HLA class I and class II repertoire of an individual. Using this enzyme‐linked immunospot (ELISpot) assay, we found a median frequency of 31 HLA class I and 89 HLA class II–specific memory B cells per million IgG‐producing cells directed at paternal HLA in peripheral blood samples from women (n = 22) with a history of pregnancy, using cell lysates from spouses. The donor‐specific memory B cell ELISpot can be used in HLA diagnostic laboratories as a cross‐match assay to quantify donor‐specific memory B cells in patients with a history of sensitizing events. Abstract : A novel assay enables the quantification of donor HLA‐specific memory B cells in peripheral blood of immunized individuals using cell lysates as a natural source of both donor‐derived HLA class I and class II.